Association between health behaviours and cardiometabolic dysregulation: a population-based survey among healthy adults in Hong Kong - Yu, Esther Yee Tak (BMJ Open, 2021)
OBJECTIVE: To explore the association between cardiometabolic dysregulation, an integral component of allostatic load, and health risk behaviours (HRBs) of the Hong Kong healthy adult population. DESIGN: Secondary analysis of cross-sectional anonymous data. SETTING: Data on sociodemographics, self-reported health status, HRBs and biomarkers were extracted from the Hong Kong Population Health Survey 2014/2015. PARTICIPANTS: One thousand five hundred and fifty-one participants aged 18–64 years without self-reported diagnoses of hypertension, diabetes mellitus, hyperlipidaemia, cardiovascular disease, cognitive impairment or cancer. PRIMARY OUTCOME MEASURES: Cardiometabolic dysregulation index (CMDI), ranging from 0 to 6, was calculated by counting the number of biomarkers including systolic blood pressure, diastolic blood pressure, waist to hip ratio, glycated haemoglobin, total cholesterol to high-density lipoprotein cholesterol ratio, and triglycerides that were above the respective normal level suggested by international guidelines and literature. HRBs including smoking, dietary habits and sleeping hours were collected by self-report questionnaire. Alcohol consumption was assessed by the 10-item Alcohol Use Disorders Identification Test, while physical activity level was measured using the Global Physical Activity Questionnaire. A composite HRB score, ranging from 0 to 5, was calculated as the cumulative number of HRBs. The effect of HRB on CMDI was evaluated by negative binomial regression with adjustment for socioeconomic status, health awareness and comorbidities of the participants. RESULTS: The mean CMDI of the studied population was 1.6; 29.5% had a CMDI of 0, whereas 1.5% had a CMDI of 6. Significant difference was observed in mean CMDI between gender and different age groups. Sleeping less than 6 hours (incidence rate ratio (IRR)=1.26, p<0.001), smoking (IRR=1.15, p=0.027), insufficient physical activity (IRR=1.12, p=0.007) and higher composite HRB score (IRR=1.12, 95% CI 1.06 to 1.18) were significantly associated with higher CMDI. CONCLUSION: Smoking, physical inactivity and inadequate sleep—an essential yet often overlooked health behaviour—were associated with higher CMDI in the Hong Kong healthy adult population.